A prospective observational cohort study to identify the causes of anaemia and association with outcome in cardiac surgical patients. Issue 2 (12th September 2014) - Hung, Matthew; Ortmann, Erik; Besser, Martin; Martin-Cabrera, Pedro; Richards, Toby; Ghosh, Marcus; Bottrill, Fiona; Collier, Timothy; Klein, Andrew A
Abstract : Objectives: Preoperative anaemia is associated with increased morbidity and mortality. We sought to determine the relative frequencies of the different causes of anaemia including absolute and functional iron deficiency, and the association of different haematological parameters, including plasma hepcidin, a key protein responsible for iron regulation, with outcomes after cardiac surgery. Methods: Prospective observational study between January 2012 and 2013; 200 anaemic cardiac surgical patients were recruited and 165 were studied. Detailed blood and bone marrow analysis was performed. Primary outcome was days alive and out of hospital. Results: Mean (SD) haemoglobin (Hb) was 102 (8) g/L for women and 112 (11) g/L for men. Regarding outcomes, 137 (83%) patients were transfused at least one unit of red blood cells; 30-day mortality was 1.8% (three patients). Functional iron deficiency was diagnosed in 78 patients (47%). Plasma hepcidin concentration was the only haematological variable associated with outcome, with mean days alive and out of hospital 2.7 (95% CI 0.4 to 5.1) days less if hepcidin ≥20 ng/mL compared with <20 ng/mL (p=0.024). Multivariable analysis showed that the association between hepcidin and outcome was independent of risk (European System for Cardiac Operative Risk Evaluation), transfusion and Hb. Conclusions: Functional iron deficiency was the most common cause of anaemia but was not associated with outcome. The only haematological parameter that was associated with outcome was hepcidin concentration, which is a novel finding and introduces further complexity into our understanding of the role of iron and its regulation by hepcidin. We propose that future research should target patients with elevated hepcidin.